Focused ultrasound extraction (FUSE) for the rapid extraction of DNA from tissue matrices. Issue 12 (20th October 2020) - Holmes, Hal R.; Haywood, Morgan; Hutchison, Ruby; Zhang, Qian; Edsall, Connor; Hall, Timothy L.; Baisch, David; Holliday, Jason; Vlaisavljevich, Eli
Abstract: Rapid DNA extraction is a critical barrier for routine and fieldable genetics tests for applications in conservation, such as illegal trafficking and fraudulent mislabelling. Here, we develop a non‐thermal focused ultrasound extraction (FUSE) technique that creates a dense cloud of high‐pressure acoustic cavitation bubbles to disintegrate targeted tissues into an acellular debris, resulting in the rapid release of entrapped DNA. In this work, we demonstrate the proof‐of‐concept of the FUSE technique by obtaining species identifiable sequences and shotgun sequencing reads from DNA extracted from Atlantic salmon Salmo salar tissues. Having mitigated the key risks for this technique, we hypothesize future developments with this technology can be applied to accelerate and simplify DNA extraction from exceedingly difficult samples with complex tissue matrices (i.e. fibrous tissue and timber samples) in both laboratory and field settings.